GAMIFIED LEARNING ENVIRONMENT BY UTILZING BAMBOOZLE FOR EFL : SECONDARY TEACHER & STUDENTS’ VOICE - LESTARI, FETI; HIDAYANI, SELNISTIA; OKTAVIANA, FADILLAH (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This study comperhends the Student and Teacher perspective by utilizing Bamboozle platforms in EFL Secondary Classroom. This study is designed by applying qualitative approach. The data sources taken in one of the school in Banten Province. Georaphically supported and facilitated by technology and also boosted by the needs of the curriculum to advance the technological context. The English teacher and Eive Students were Semi Structured Interviewed and observed, supported by the documentation. The data analyzed by using thematic analysis shows that, the study highlights students' increased readiness to speak in English. Because of Bamboozle's gamiEication, users are more motivated and engaged, which promotes a more positive attitude toward language learning. The study also reveals how to create a fun learning environment. With its dynamic and comfortable environment, Bamboozle's interactive features and adaptive design accommodate a wide range of learning preferences, allowing students to progress through language lessons at their own speed. Furthermore, studies show that incorporating Bamboozle into the classroom makes it easier for teachers to manage. The platform's Elexible tools and easy-to-use interface help teachers organize and run their classes effectively. Teachers are able to concentrate on providing high-quality instruction, encouraging effective communication, and customizing lessons to Eit the speciEic requirements of EFL learners because of this streamlining effect.